Unexpected Complication of Blunt Trauma: Evisceration - Emel Ulusoy; Bengü Serpen; Fatma Akgül; Hale Çitlenbik; Didem Yılmaz Sönmez; Osman Zeki Karakuş; Durgül Yılmaz; Murat Duman (Galenos Yayinevi, 2018)
Traumatic abdominal wall hernia with evisceration is an uncommon injury secondary to blunt abdominal trauma in all age groups. Bicycle handlebar injuries among children are significant causes of blunt abdominal trauma such as penetrating trauma. We present a case of evisceration in a 14-year-old child after blunt injury with handle bar. We assume that early management and prompt abdominal exploration and surgical repair provide good clinical outcome without complication.